Diffraction diamond grating formed by silver-ion mask implantation. (June 2019) - Stepanov, A.L.; Nuzhdin, V.I.; Kazuchits, N.M.; Valeev, V.F.
Highlights: Low energy Implantation of diamond with Ag + through a surface mask was used. Ag nanoparticle formation and ion etching of the diamond surface are realized. A diffraction grating microstructure was obtained on the surface of the diamond.